Acute Dietary Protein Intake Restriction Is Associated with Changes in Myostatin Expression after a Single Bout of Resistance Exercise in Healthy Young Men. Issue 2 (4th December 2013) - Snijders, Tim; Verdijk, Lex B.; McKay, Bryon R.; Smeets, Joey S.J.; van Kranenburg, Janneau; Groen, Bart B.B.; Parise, Gianni; Greenhaff, Paul; van Loon, Luc J.C.
Abstract: Skeletal muscle satellite cells (SCs) play an important role in the myogenic adaptive response to exercise. It remains to be established whether nutrition plays a role in SC activation in response to exercise. In the present study, we assessed whether dietary protein alters the SC response to a single bout of resistance exercise. Twenty healthy young (aged 21 ± 2 y) males were randomly assigned to consume a 4-d controlled diet that provided either 1.2 g protein ⋅ kg body weight −1 ⋅ d −1 [normal protein diet (NPD)] or 0.1 g protein ⋅ kg body weight −1 ⋅ d −1 [low protein diet (LPD)]. On the second day of the controlled diet, participants performed a single bout of resistance exercise. Muscle biopsies from the vastus lateralis were collected before and after 12, 24, 48, and 72 h of post-exercise recovery. SC content and activation status were determined using immunohistochemistry. Protein and mRNA expression were determined using Western blotting and reverse transcription polymerase chain reaction. The number of myostatin + SCs decreased significantly at 12, 24, and 48 h (range, −14 to −49%; P < 0.05) after exercise cessation, with no differences between groups. Although the number of myostatin + SCs returned to baseline in the type II fibers on the NPD after 72 h of recovery, the number remained low on the LPD. At the 48 and 72 h time points, myostatin protein expression was elevated (86 ± 26% and 88 ± 29%, respectively) on the NPD ( P < 0.05), whereas it was reduced at 72 h (−36 ± 12% compared with baseline) in the LPD group ( P < 0.05). This study demonstrates that dietary protein intake does not modulate the post-exercise increase in SC content but modifies myostatin expression in skeletal muscle tissue. This trial was registered at clinicaltrials.gov as NCT01220037.